Grey Matter Heterotopia and Criminal Responsibility in a Case of Personal Injury Defense - Curci, Antonietta; Rampino, Antonio (Frontiers in Psychiatry, 2020)
The abnormal allocation of nodules of grey matter in areas of the brain or spinal cord that should physiologically be occupied by white matter characterizes a neural defect called Grey Matter Heterotopia (GMH). The improvement of MRI techniques has enabled a deeper understanding of the neuropathological bases and epidemiology of such a condition. Among its major manifestations, there is the onset of epileptic seizures, mild intellectual disability, impairments in executive functioning, neurodevelopmental disorders; less frequently GMH has been found associated with depression, anxiety, and schizophrenia. Despite the clinical interest in GMH, no studies have considered the possible forensic and criminological implications of this condition. In the current study, we present a case of GMH in a young male defendant accused of having seriously injured a schoolmate as a reaction to bullying behaviour. Neuropsychological and instrumental evidence converge in showing prevalence for the defendant’s adoption of repressive responses to stressors, and difficulties to inhibit undesirable behaviour at the long run. In the case at hand, the massive stress induced by the exposition to bullying behaviour undermined inhibitory control, hence an impulsive and disproportionate reaction took place. Without appropriate therapeutic control, this reactive behaviour might take place again. As a consequence, the forensic assessment recommended that the defendant was held partially liable only but that there was likelihood of recidivism. We discuss this single-case evidence for a possible role of GMH in the adoption of dyscontrolled responses to stressors, and the relevance of GMH diagnosis in forensic proceedings.